2013
DOI: 10.1103/physrevb.88.115427
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of nanometer-scale confinement of plasmonic eigenmodes responsible for hot spots in random metallic films

Abstract: We report on the identification and nanometer scale characterization over a large energy range of random, disorder-driven, surface plasmons in silver semicontinuous films embedded in silicon nitride. By performing spatially resolved electron energy loss spectroscopy experiments, we experimentally demonstrate that these plasmons eigenmodes arise when the films become fractal, leading to the emergence of strong electrical fields ("hot spots") localized over few nanometers. We show that disorder-driven surface pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 39 publications
3
53
0
Order By: Relevance
“…To further illustrate this, we consider a randomly generated nanostructure consisting of 29 gold nanospheres (diameter D = 9 nm) partially or almost completely overlapping and located on a glass substrate ( figure 4(a)). Such a morphology mimicks the nanoporous metallic films recently investigated by combined STEM-EELS and high-angle annular dark-field microscopy (HAADF) (Bosman et al 2011, Losquin et al 2013. The latter studies have demonstrated that the peculiar optical properties of nanoporous metallic films originate from nanoscale variations of the number and spectral properties of the surface plasmon resonances supported by these complex objects with no clear correlation with their local morphology.…”
Section: Electron Energy Losses From Nanostructures Of Arbitrary Geommentioning
confidence: 82%
“…To further illustrate this, we consider a randomly generated nanostructure consisting of 29 gold nanospheres (diameter D = 9 nm) partially or almost completely overlapping and located on a glass substrate ( figure 4(a)). Such a morphology mimicks the nanoporous metallic films recently investigated by combined STEM-EELS and high-angle annular dark-field microscopy (HAADF) (Bosman et al 2011, Losquin et al 2013. The latter studies have demonstrated that the peculiar optical properties of nanoporous metallic films originate from nanoscale variations of the number and spectral properties of the surface plasmon resonances supported by these complex objects with no clear correlation with their local morphology.…”
Section: Electron Energy Losses From Nanostructures Of Arbitrary Geommentioning
confidence: 82%
“…1. Moreover collective effects due to NPs dipolar coupling between nearby NPs could be also referred to because they also lead to a redshift of the LSPR15. Important to note is the fact that the T mode of the LSPR remains at the vicinity of 530 nm for all the deposits ensuring their resonant excitation with the 531 nm laser line.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have concerned their structural and optical properties (for a recent review, see Kossov et al 131415 and thus their application as surface-enhanced Raman scattering (SERS) substrates16.…”
mentioning
confidence: 99%
“…11 Recently, semi-continuous metal films have attracted renewed interest due to the huge local field enhancement regions (hot spots) within the spectral range of the particle plasmon resonances. [12][13][14][15][16][17] Both the density and the intensity of the hot spots are found to increase when approaching the percolation threshold 16 before decreasing in the metallic phase. It has been revealed that the optical modes are of different nature when the particles are isolated or when the layer is at percolation.…”
mentioning
confidence: 93%